Characterisation of current and turbulence in the FloWave Ocean Energy Research Facility. (15th July 2017) - Sutherland, Duncan R.J.; Noble, Donald R.; Steynor, Jeffrey; Davey, Thomas; Bruce, Tom
Abstract: Tidal energy is a developing industry and requires high precision test facilities which replicate the full-scale flows as accurately as possible to develop new technologies. In particular, the spatial and temporal variation must be well understood. FloWave is a state-of-the-art test facility with the ability to produce multi-directional waves and currents. This work investigates the mean and turbulent flow parameters throughout the tank using an ADV. The goal is to provide a comprehensive characterisation of the flow in the tank, in a robust and repeatable manner. These flow parameters are then compared to sample data from field measurements for context. The turbulence intensities are normally distributed in the range of 5–11% and integral lengthscales were log-normally distributed over a 0.18–0.41 m range across the test area. The Reynolds stresses showed the streamwise-vertical pair were relatively constant throughout the depth, with values in the range −0.31 to 0.15 Pa, while the transverse-vertical pair show high vertical variation with values of −1.35 to 0.20 Pa. For the majority of locations the flow metrics are generally realistic compared with those measured at the Fall of Warness site. This work improves the understanding of flow behaviour in the tank, facilitating higher confidence testing of scaled devices. Abstract : Highlights: An overview of the spatial variation of mean flow and turbulence metrics from the FloWave combined wave and current test facility. Metrics show variation across all directions, but are within a reasonable range in the test area. Metrics are shown in the main to be comparable to those measured at real tidal sites.